Staphylococcus aureus Biofilms and Their Response to a Relevant in vivo Iron Source - Dauros-Singorenko, Priscila; Wiles, Siouxsie; Swift, Simon (Frontiers in Microbiology, 2020)
Biofilm infections can be chronic, life threatening and challenging to eradicate. Understanding in vivo stimuli affecting the biofilm cycle is one step towards targeted prevention strategies. Iron restriction by the host is a stimulus for biofilm formation for some Staphylococcus aureus isolates, however in some infection scenarios bacteria are exposed to abundant amounts of haemoglobin, which S. aureus is able to use as iron source. Thus we hypothesized a role for haemoglobin in the biofilm infection. Microplate “biofilm” assays showed biofilm PIA-matrix production was increased in the presence of haemoglobin when compared to the provision of iron as an inorganic salt. Microscopic analysis of biofilms showed that the provision of iron as haemoglobin consistently caused thicker and more structured biofilms when compared to the effect of the inorganic iron source. Iron responsive biofilm gene expression analysis showed that Agr Quorum Sensing, a known biofilm dispersal marker, was repressed with haemoglobin but induced with an equivalent amount of inorganic iron in the laboratory strain Newman. The gene expression of two biofilm structuring agents, PSMα and PSMβ, differed in the response to the iron source provided and was not correlated to haemoglobin-structured biofilms. A comparison of the model pathogen S. aureus Newman with local clinical isolates demonstrated that while there was a similar phenotypic biofilm response to haemoglobin, there was substantial variation in the expression of key biofilm dispersal markers, suggesting an underappreciated variation in biofilm regulome among S. aureus isolates and that no general inferences can be made by studying the behaviour of single strains.